Analisis Perbedaan Abnormal Return dan Cumulative Abnormal Return Emiten Sektor Keuangan Sekitar Pemilu 17 April 2019 - Cahyono Jagad Raya; R.A Sista Paramita (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
This research was prepared using the event study method to analyze the Indonesian capital market reaction to a political event that can be seen from differences in abnormal returns and cumulative abnormal returns of shares before and after the general election event on 17 April 2019. The observation period carried out for 11 days consisted of 5 days before the event date, one-day event date, and 5 days after the event date. The population of the data used are financial sector companies listed in the period January to April 2019 on the Indonesia Stock Exchange, then the sample was taken using a purposive sampling obtained as many as 73 of 91 companies. While the data amalgamation technique uses the Wilcoxon Signed Rank Test because the data used doesnt meet the assumption of normality. The results showed that there were no differences in abnormal returns and cumulative abnormal returns of financial sector issuers between before and after the general election 17 April 2019. Therefore, the general election 17 April 2019 didnt contain important information for market participants so the market didnt overreact.